Transformation of the Peregrine Breather Into Gray Solitons on a Vertically Sheared Current - Hsu, H. C.; Abid, M.; Chen, Y. Y.; Kharif, C. (Frontiers in Physics, 2021)
In this Brief Research Report, we show, within the framework of the nonlinear Schrödinger equation in deep water and in the presence of vorticity (vor-NLS), that the Peregrine breather traveling at the free surface of a shear current of slowly varying vorticity may transform into gray solitons.